Conversations across our America : talking about immigration and the Latinoization of the United States - Mendoza, Louis Gerard, 1960- (Joe R. and Teresa Lozano Long series in Latin American and Latino art and culture., 2012)
In the summer of 2007, Louis G. Mendoza set off on a bicycle trip across the United States with the intention of conducting a series of interviews along the way. Wanting to move beyond the media?s limited portrayal of immigration as a conflict between newcomers and "citizens," he began speaking with people from all walks of life about their views on Latino immigration. From the tremendous number of oral histories Mendoza amassed, the resulting collection offers conversations with forty-three different people who speak of how they came to be here and why they made the journey. They touch upon how Latino immigration is changing in this country, and how this country is being changed by Latinoization. Interviewees reflect upon the concerns and fears they?ve encountered about the transformation of the national culture, and they relate their own experiences of living and working as "other" in the United States. Mendoza?s collection is unique in its vastness. His subjects are from big cities and small towns. They are male and female, young and old, affluent and impoverished. Many are political, striving to change the situation of Latina/os in this country, but others are "everyday people," reflecting upon their lives in this country and on the lives they left behind. Mendoza?s inclusion of this broad swath of voices begins to reflect the diverse nature of Latino immigration in the United States today.